Penerapan Case Based Reasoning (Cbr) Pada Sistem Pakar Diagnosa Penyakit Otitis Media Supuratif Kronis (OMSK) Pada Orang Dewasa - Triswardani, Gita; Hasibuan, Nelly Astuti (STMIK Budi Darma, 2018)
Chronic Suppurative Otitis Media (OMSK) is an infection of middle ear mucosal inflammation with perforated tympanic membrane and secret from the ear continuously, formerly called otitis media perforate (OMP) in everyday congek. Chronic suppurative otitis media (OMSK) is commonly found in lower middle-class people, and leads to increased costs for treatment. Therefore required a tool or system that has the ability of a doctor in diagnosing the disease. The expert system is used not to replace the physician's function but will be used only as a complement to a system and aids. An expert system is a system capable of mimicking the reasoning of a computer expert to solve problems as is usually done by experts. The method used in this expert system uses case-based reasoning (CBR) method, since this method yields the value of kmiripan a case with the former by recalling similar events that have occurred in the past then use the knowledge or information to solve a new problem, or in other words solve the problem by adopting solutions that have been used in the past.